Cerâmicas odontológicas: propriedades, indicações e considerações clinicas - Amoroso, Andressa Paschoal [UNESP]; Ferreira, Mayara Barbosa [UNESP]; Torcato, Leonardo Bueno [UNESP]; Pellizzer, Eduardo Piza [UNESP]; Mazaro, José Vitor Quinelli [UNESP]; Gennari Filho, Humberto [UNESP] (My University, 2012)
The demand for esthetic restorations has resulted in an increased use of dental ceramics and is the main alternative restorative material to tooth structure due to its favorable properties. Therefore, the aim of this work is to study the evolution of ceramic systems, involving different types and properties, indications, and clinical issues as aesthetic, cementing and longevity. In a detailed and advanced search in the database PubMed, 98 articles were found using the following key words: dental porcelain dental all-ceramic and ceramic according to the criteria for inclusion and exclusion left only 35 articles for review. Several ceramic systems are available in the market, making the prosthetic professionals need a constant recycling about their properties and directions, since good results are due to the selection of the best material for a particular case in all the skill of the practitioner.

A demanda por restaurações estéticas tem resultado em um aumento do uso de cerâmicas dentais, constituindo a principal alternativa de material restaurador para a estrutura dental devido as suas propriedades favoráveis. Com isso, o objetivo desse trabalho será estudar, através de uma revisão de literatura, a evolução dos sistemas cerâmicos, envolvendo os diferentes tipos e propriedades, indicações e considerações clínicas. Em uma busca detalhada e avançada no banco de dados PubMed, foram encontrados 98 artigos utilizando os seguintes descritores: dental porcelain, dental ceramic e all-ceramic, de acordo com os critérios de inclusão e exclusão restaram apenas 35 artigos para a revisão. Diversos sistemas cerâmicos estão disponíveis no mercado, fazendo com que os profissionais da área protética necessitem de uma constante reciclagem acerca das suas propriedades e indicações, visto que bons resultados são devidos à seleção do melhor material para determinado caso em conjunto à habilidade do profissional.
Dental ceramics: properties, indications and clinical considerations
Keywords: Dental prothesis; Dental porcelain; Odontoligic ceramic; Porcelana dental; Cerâmica dental; Cerâmicas odontológicas